P53, epidermal growth factor, and platelet-derived growth factor in uterine leiomyosarcoma and leiomyomas. Issue 2 (1st March 2006) - Anderson, S. E.; Nonaka, D.; Chuai, S.; Olshen, A. B.; Chi, D.; Sabbatini, P.; Soslow, R. A.
Abstract : Uterine leiomyosarcoma (ULMS) is an aggressive gynecological disease. Although ULMS are often found in association with benign leiomyoma (LMA), little is known regarding the relationship between these benign and malignant smooth muscle neoplasms. The objective of this study was to evaluate the expression of epidermal growth factor (EGFR), platelet-derived growth factor (PDGFR), and p53 in ULMS specimens, their prognostic relevance, and the expression of these molecular markers when compared to benign LMA specimens. Between 1991 and 2001, 25 patients were identified with high-grade primary ULMS and for whom tissue was available. Tissue microarray was created with three representative cores from each of the ULMS cases as well as from 19 patients with benign uterine leiomyomata. Immunohistochemical (IHC) staining was performed for EGFR, PDGFR, and p53. Negative and positive IHC staining was scored for each marker. Outcome analysis was performed only for ULMS. Survival was determined from the time of initial diagnosis to last follow-up. Twelve (48%) ULMS expressed p53 compared to none of the LMA ( P < 0.001), and 15 (60%) ULMS cases showed PDGFR expression compared to 32% of LMA samples ( P = 0.08). EGFR expression did not differ between ULMS and LMA groups. ULMS patients with p53 expression had a poorer survival compared to ULMS patients with negative expression ( P = 0.07). ULMS tumor stage had the strongest association with overall survival ( P = 0.05). Our study supports previous investigations indicating that p53 expression may serve as a prognostic marker for ULMS patients. The difference in PDGFR expression between ULMS and LMA demonstrated a trend toward significance. EGFR was not commonly expressed in ULMS. These uniquely expressed markers may assist in stratifying patients by survival and identify novel therapeutic markers. Clearly, further investigation is needed.